PENGARUH FAKTOR-FAKTOR KONTEKSTUAL TERHADAP PERSEPSIAN PENYERAPAN ANGGARAN TERKAIT PENGADAAN BARANG/JASA - Juliani, Dian; Sholihin, Mahfud (Jurnal Akuntansi dan Keuangan Indonesia, 2014)
This study examines the effect of contextual factors such as knowledge of regulatory, management commitment, and environmental bureaucracy on budget absorption related to the procurement of goods/services. Institutional theory and expectancy theory are used to explain the phenomenon of budget absorption related to the procurement of goods/services. This study uses mixed method with sequential explanatory design. The samples in this study were employees who had a certificate of the procurement of goods/services at 152 SKPD in the area of D. I. Yogyakarta. The results of quantitative analysis in this study showed that knowledge of regulatory, management commitment, and environmental bureaucracy have positive effect on the budget absorption related to the procurement of goods/services. The results of the qualitative analysis also support the quantitative results based on interviews conducted in the selected respondents. The major contribution of this study is to provide an understanding of the factors that influence the absorption related to the procurement of good/services, so it can be used to formulate policies and improvements in the procurement of goods/services.